Polyester film and use thereof

By using polyester films with refractive index and thickness within a specific range, and layering hard coating or adhesive layers on them, the problem of image distortion and surface protection films prone to cracking during repeated folding is solved, and the problem of folded displays is achieved. High durability and no image distortion effects.

CN119391146APending Publication Date: 2025-02-07TOYOBO CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411419705.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2019-07-12
Filing Date
2020-01-15
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing foldable displays are prone to image distortion during repeated folding, and the surface protective film is prone to cracks and fractures in the folded part.

Method used

A polyester film having a thickness of 10 to 80 μm was used, with a refractive index of 1.590 to 1.620 in the bending direction, a refractive index of 1.670 to 1.700 in the folding direction, and a refractive index of 1.520 or less in the thickness direction, and a layer on the polyester film. Hard coating or adhesive layer to improve its durability and protection.

Benefits of technology

It is achieved that there is no crack or breakage in the folded part, the film will not deform after repeated folding, the display image will not be distorted, and the mobile terminal device provides beautiful images and excellent convenience.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119391146A_ABST
    Figure CN119391146A_ABST
Patent Text Reader

Abstract

[Problem] To provide a folding-type display which has excellent mass productivity and does not worry about distortion of an image displayed on a folded portion after repeated bending, and to provide a polyester film for a folding-type display in which cracks do not occur in a folded portion, and a use thereof. [Solution] A polyester film for a folded display, which is a polyester film having a thickness of 10-80 [mu] m and which satisfies the following conditions. (1) The refractive index in the bending direction is 1.590 to 1.620. (2) The refractive index in the direction of the folded portion is 1.670 to 1.700. (3) The refractive index in the thickness direction is 1.520 or less. (4) The density is 1.380 g / cm3 or more (Here, the bending direction refers to a direction orthogonal to a folded portion when the polyester film is folded. ).
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of an application with a filing date of January 15, 2020, application number 2020800125072, and invention name “polyester film and its use”. Technical Field

[0002] The present invention relates to a polyester film for a foldable display, a hard coating film for a foldable display, a laminated film for a foldable display, a foldable display, and a mobile terminal device, and relates to a foldable display and a mobile terminal device that are not prone to image distortion caused by film deformation even when repeatedly folded, and the aforementioned polyester film, hard coating film and laminated film for a foldable display. Background Art

[0003] As the lightweight of mobile terminal devices is promoted, mobile terminal devices represented by smartphones have become widely popular. Mobile terminal devices are required to have various functions, but also convenience. Therefore, in popular mobile terminal devices, it is assumed that they can be easily operated with one hand and can be stored in a pocket of clothes, so a small screen size of about 6 inches is sometimes required.

[0004] On the other hand, tablet terminals with a screen size of 7 to 10 inches are expected to be used not only for video content and music but also for business purposes, drawing purposes, reading, etc., and have high functionality. However, they cannot be operated with one hand and have poor mobility, which poses a problem in terms of convenience.

[0005] In order to achieve these problems, a method of connecting a plurality of displays to make them compact has been proposed (see Patent Document 1). However, since the frame portion remains, the image is interrupted, and visibility is reduced, which has not yet become popular.

[0006] Therefore, in recent years, mobile terminals equipped with flexible displays or foldable displays have been proposed. In this way, the image is not interrupted, and the convenience of carrying the mobile terminal device equipped with a large-screen display is good.

[0007] Here, regarding the existing display and mobile terminal device that do not have a folding structure, the surface of the display can be protected by non-flexible raw materials such as glass, but in the case of a folding display, in the case of a display formed on one side by a folding portion, it is necessary to use a hard coating film that is flexible and can protect the surface. However, in a folding display, since the part in the fixed folding part is repeatedly bent, the film in this part deforms over time, and there are problems such as distortion of the image displayed on the display. In addition, not only the surface protection film, but also in the folding display, a film is used in various parts such as a polarizing plate, a phase difference plate, a touch panel substrate, a substrate of a display unit such as an organic EL, and a protective component on the back, and these films are also required to have durability against repeated folding.

[0008] Therefore, a method of partially changing the film thickness has been proposed (see Patent Document 2), but there is a problem of lack of mass productivity.

[0009] In addition, a method of adjusting the refractive index of the polyester film in the bending direction has been proposed (see Patent Document 3), but there is a problem that as the refractive index in the bending direction is reduced, the pencil hardness during hard coating is reduced, and the surface protection function of the display is reduced. In addition, there is a problem that if the refractive index in one direction is reduced, the deformation during folding is improved, but the uniaxial orientation in the folding direction is increased, and cracks or breaks occur in the folded portion.

[0010] Prior art literature

[0011] Patent Literature

[0012] Patent Document 1: Japanese Patent Application Publication No. 2010-228391

[0013] Patent Document 2: Japanese Patent Application Publication No. 2016-155124

[0014] Patent Document 3: International Publication No. 2018 / 150940 Summary of the invention

[0015] Problem that the invention aims to solve

[0016] The present invention aims to solve the problems of the components of the above-mentioned existing displays, and in order to provide a foldable display with excellent mass producibility and no worries about distortion of the image displayed on the folded portion after repeated bending, and a mobile terminal device equipped with such a foldable display, it is intended to provide a polyester film for a foldable display, a hard coating film for a foldable display, and a laminated film for a foldable display that will not have creases and cracks in the folding portion.

[0017] Solutions for solving problems

[0018] That is, the present invention includes the following configurations.

[0019] 1. A polyester film for a foldable display, which is a polyester film having a thickness of 10 to 80 μm and satisfies the following conditions.

[0020] (1) The refractive index in the bending direction is 1.590 to 1.620

[0021] (2) The refractive index in the direction of the folded portion is 1.670 to 1.700

[0022] (3) The refractive index in the thickness direction is 1.520 or less

[0023] (4) Density: 1.380 g / cm 3 above

[0024] (Here, the bending direction refers to a direction perpendicular to the folded portion when the polyester film is folded.)

[0025] 2. The polyester film for foldable displays according to item 1 above, which has a total light transmittance of 85% or more, a haze of 3% or less, and a maximum heat shrinkage of 6% or less.

[0026] 3. The polyester film for foldable displays according to the first or second aspect, wherein the polyester film has an easy-adhesion layer on at least one surface thereof.

[0027] 4. The polyester film for a foldable display according to any one of Items 1 to 3, wherein the in-plane retardation (Re) is 3,000 to 30,000 nm.

[0028] 5. A hard coat film for a foldable display, comprising a hard coat layer having a thickness of 1 to 50 μm on at least one surface of the polyester film for a foldable display according to any one of the first to fourth items.

[0029] 6. The hard coat film for a foldable display according to item 5 above, wherein the total light transmittance is 85% or more.

[0030] 7. The hard coat film for a foldable display according to item 5 or 6, wherein the elastic modulus of the polyester film in the bending direction is 2.7 GPa or less, and the elastic modulus in the direction of the folded portion is 4.5 GPa or more.

[0031] 8. The hard coat film for a foldable display according to any one of Items 5 to 7, wherein the haze is 3% or less.

[0032] 9. A laminate film for a foldable display, comprising an adhesive layer on the surface opposite to the surface having the hard coat layer of the hard coat film according to any one of items 5 to 8 above.

[0033] 10. The laminate film for a foldable display according to item 9 above, wherein the thickness of the adhesive layer is 1 to 50 μm.

[0034] 11. A foldable display, wherein the hard coating film for a foldable display described in any one of items 5 to 8 is arranged as a surface protection film in such a manner that the hard coating layer is located on the surface, and a continuous single hard coating film foldable display is arranged via a folding portion of the foldable display.

[0035] 12. A foldable display, wherein the laminate film for a foldable display described in item 9 or 10 is arranged as a surface protection film in such a manner that a hard coating layer is located on the surface, and a continuous single laminate film is arranged via a folding portion of the foldable display.

[0036] 13. A mobile terminal device having the foldable display described in item 11 or 12 above.

[0037] Effects of the Invention

[0038] The polyester film for foldable display, hard coating film, and foldable display using the laminated film of the present invention maintain mass production and the polyester film does not crack at the folded portion, does not deform after repeated folding, and does not cause image distortion at the folded portion of the display. Mobile terminal devices equipped with foldable displays using the aforementioned polyester film or hard coating film provide beautiful images, are rich in functionality, and are also excellent in convenience such as portability. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 It is a schematic diagram for illustrating the bending radius when the foldable display of the present invention is folded.

[0040] Figure 2 This is a schematic diagram for illustrating the bending direction of the polyester film for a foldable display of the present invention. DETAILED DESCRIPTION

[0041] (monitor)

[0042] The display referred to in the present invention refers to all display devices. The types of displays include LCD, organic EL display, inorganic EL display, LED, FED, etc., but LCD, organic EL, and inorganic EL having a bendable structure are preferred. In particular, organic EL and inorganic EL that can reduce the layer structure are particularly preferred, and organic EL with a wide color gamut is further preferred.

[0043] (Foldable Display)

[0044] For a foldable display, a continuous single display can be folded in half or the like when moving. By folding, the size is reduced by half, and mobility can be improved. The bending radius of the foldable display is preferably 5 mm or less, and more preferably 3 mm or less. When the bending radius is 5 mm or less, thinning in the folded state becomes possible. It can be said that the smaller the bending radius, the better, but the smaller the bending radius, the easier it is to produce creases. The bending radius is preferably 0.1 mm or more, and can be 0.5 mm or more, and can be 1 mm or more. Even if the bending radius is 1 mm or more, thinning sufficient for practical use when moving can be achieved. The bending radius when folded refers to the measurement of the bending radius. Figure 1 The radius of the inner side of the folded portion when folded is obtained from the position of the symbol 11 in the schematic diagram. It should be noted that the surface protection film described later may be located on the outer side or the inner side of the folded foldable display.

[0045] In addition, the foldable display may be folded in three or four, or may be a so-called rollable type, all of which are included in the scope of the foldable display of the present invention.

[0046] When the polyester film for foldable display of the present invention is a component of a foldable display, it can be used in any part. Hereinafter, taking an organic EL display as an example, a representative structure of a foldable display and a part where the polyester film of the present invention can be used are described. It should be noted that, hereinafter, the polyester film for foldable display of the present invention is sometimes referred to as the polyester film of the present invention.

[0047] (Foldable organic EL display)

[0048] The essential components of the foldable organic EL display are an organic EL component, but a circular polarizing plate, a touch panel component, a surface protection film, a back protection film, etc. may be further provided as necessary.

[0049] (Organic EL components)

[0050] The general structure of an organic EL component includes: electrode / electron transport layer / luminescent layer / hole transport layer / transparent electrode. As a substrate for providing an electrode, and further providing an electron transport layer, a luminescent layer, and a hole transport layer, the polyester film of the present invention can be used. In particular, it can be preferably used as a substrate for a transparent electrode. In this case, the substrate film requires high barrier properties against water vapor and oxygen, so it is preferred to provide a barrier layer such as a metal oxide layer on the polyester film of the present invention. In order to improve the barrier properties, a plurality of barrier layers can be provided, or a plurality of polyester films provided with barrier layers can be used.

[0051] (Touch Panel Assembly)

[0052] The mobile terminal device preferably has a touch panel. When an organic EL display is used, a touch panel component is preferably arranged on the upper part of the organic EL display or between the organic EL component / circular polarizer. The touch panel component has a transparent substrate such as a film and a transparent electrode arranged thereon. The polyester film of the present invention can be used as the transparent substrate. When used as a transparent substrate of a touch panel, a hard coating layer and a refractive index adjustment layer are preferably provided on the polyester film.

[0053] (Circular polarizing plate)

[0054] The circular polarizer suppresses the external light from being reflected by the components inside the display and reducing the image quality. The circular polarizer has a linear polarizer and a phase difference plate. The linear polarizer has a protective film on at least the viewing side of the polarizer. The polarizer may also have a protective film on the surface opposite to the viewing side, or a phase difference plate may be directly laminated on the polarizer. The phase difference plate can use a resin film having a phase difference such as polycarbonate or cyclic olefin, or a phase difference layer containing a liquid crystal compound on the resin film. The polyester film of the present invention can be used as a polarizer protective film or a resin film of a phase difference plate. In these cases, the polyester film of the present invention preferably has a slow axis direction parallel to or orthogonal to the absorption axis direction of the polarizer. It should be noted that for this parallel or orthogonal, a deviation within 10 degrees, preferably 5 degrees, is allowed.

[0055] (Surface protection film)

[0056] When an impact is applied to the display from above, there is a concern that the circuit of the organic EL component and the touch panel component may be broken, so in most cases, a surface protection film is provided. The polyester film of the present invention can be used as the surface protection film. The surface protection film includes a surface protection film called a cover window installed on the outermost surface of the display, and a replaceable surface protection film called after that can be pasted and peeled by the user himself, and the polyester film of the present invention can be used. When the polyester film of the present invention is used as a surface protection film, it is preferably laminated with a hard coating layer on at least the surface side of the polyester film. The hard coating layer is provided on the surface of the foldable display as the viewing side. It should be noted that the hard coating layer can also be provided on both sides.

[0057] (Back protection film)

[0058] It is also preferable to provide a protective film on the back side of the display. The polyester film of the present invention can be used as the protective film on the back side.

[0059] The polyester film of the present invention may be a protective film used for a location to be folded among the constituent members of a foldable display, or may be a protective film other than the above.

[0060] Among these, the polyester film of the present invention is preferably used for covering a window surface protection film, a rear surface protection film, a base film of a touch panel module, and a back surface protection film, and is more preferably used for covering a window surface protection film and a rear surface protection film.

[0061] In addition, as a foldable display, it is not necessary to use the polyester film of the present invention in all of the above-mentioned components. In the foldable display, in addition to the polyester film of the present invention, polyimide film, polyamide film, polyamideimide film, polyester film other than the polyester film of the present invention, polycarbonate film, acrylic film, triacetyl cellulose film, cycloolefin polymer film, polyphenylene sulfide film, polymethylpentene film, etc. can be appropriately used according to applicability.

[0062] The polyester film of the present invention may be a single-layer film composed of one or more polyester resins, or, when two or more polyesters are used, may be a multilayer film or a super-multilayer laminated film having a repeated structure.

[0063] Examples of the polyester resin used in the polyester film include polyethylene terephthalate, polybutylene terephthalate, polyethylene 2,6-naphthalate, or a polyester film formed of a copolymer having the constituent components of these resins as the main component. Among them, a stretched polyethylene terephthalate film is particularly preferred from the perspectives of mechanical properties, heat resistance, transparency, price, etc.

[0064] When a polyester copolymer is used in a polyester film, as the dicarboxylic acid component of the polyester, for example, aliphatic dicarboxylic acids such as adipic acid and sebacic acid; aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, phthalic acid, and 2,6-naphthalene dicarboxylic acid; polyfunctional carboxylic acids such as trimellitic acid and pyromellitic acid. In addition, as the glycol component, for example, fatty acid glycols such as ethylene glycol, diethylene glycol, 1,4-butanediol, propylene glycol, and neopentyl glycol, aromatic glycols such as terephthalic acid, alicyclic glycols such as 1,4-cyclohexanedimethanol, and polyethylene glycols with an average molecular weight of 150 to 20,000 can be cited. The mass ratio of the copolymer components of the preferred copolymer is less than 20 mass %. When it is less than 20 mass %, it is preferred to maintain the film strength, transparency, and heat resistance.

[0065] In addition, in the manufacture of polyester film, the intrinsic viscosity of at least one or more resin pellets is preferably in the range of 0.50 to 1.0 dl / g. When the intrinsic viscosity is 0.50 dl / g or more, the impact resistance of the obtained film is improved, and it is not easy to cause the internal circuit of the display to break due to external impact, which is preferred. On the other hand, when the intrinsic viscosity is 1.00 dl / g or less, the filter pressure of the molten fluid will not increase excessively, and it is easy to operate the film production stably, which is preferred.

[0066] The thickness of the polyester film is preferably 10 to 80 μm, more preferably 25 to 75 μm. When the thickness is 10 μm or more, the pencil hardness and impact resistance are improved, and when the thickness is 80 μm or less, it is advantageous for weight reduction and has excellent flexibility, processability, and operability.

[0067] The surface of the polyester film of the present invention may be smooth or may have concavoconvexities, but from the perspective of surface covering for display, it is not preferred that the optical properties be reduced due to the concavoconvexities. As for the haze, it is preferably 3% or less, more preferably 2% or less, and most preferably 1% or less. When the haze is 3% or less, the visibility of the image can be improved. The lower limit of the haze is as small as possible, but from the perspective of stable production, it is preferably 0.1% or more, and can be 0.3% or more.

[0068] As mentioned above, in order to reduce the haze, it is preferred that the surface roughness of the film is not too large. However, from the perspective of operability, as a method of forming roughness in order to impart a certain degree of slippage, particles can be blended into the polyester resin layer of the surface layer, or a coating layer containing particles can be applied in the middle of film formation to form roughness.

[0069] As a method for blending particles in the polyester resin layer, a known method can be used. For example, it can be added at any stage of the polyester production, preferably in the stage of esterification or after the end of the transesterification reaction and before the start of the polycondensation reaction, in the form of a slurry dispersed in ethylene glycol, etc., and the polycondensation reaction is promoted. In addition, it can be carried out by the following methods, etc.: a method of blending a slurry of particles dispersed in ethylene glycol or water, etc. with a polyester raw material using a kneading extruder with a vent; or a method of blending dried particles with a polyester raw material using a kneading extruder.

[0070] Among them, the following method is preferred: adding aggregated inorganic particles obtained by homogeneously dispersing them in a monomer solution that is a part of the polyester raw material and filtering them to the remainder of the polyester raw material before, during or after the esterification reaction. According to this method, since the monomer solution has a low viscosity, it is easy to homogeneously disperse the particles and filter the slurry with high precision, and when adding them to the remainder of the raw material, the particles have good dispersibility and are less likely to form new aggregates. From the above viewpoints, it is particularly preferred to add them to the remainder of the raw material in a low temperature state before the esterification reaction.

[0071] Alternatively, the number of protrusions on the film surface can be further reduced by obtaining a polyester containing particles in advance and then kneading and extruding the pellets with pellets containing no particles (masterbatch method).

[0072] The polyester film may contain various additives within a range in which the total light transmittance is maintained within a preferred range. Examples of the additives include antistatic agents, UV absorbers, and stabilizers.

[0073] The total light transmittance of the polyester film is preferably 85% or more, more preferably 87% or more. If the light transmittance is 85% or more, visibility can be fully ensured. It can be said that the higher the total light transmittance of the polyester film, the better, but from the perspective of stable production, it is preferably 99% or less, and can be 97% or less.

[0074] The maximum heat shrinkage of the polyester film after heat treatment at 150°C for 30 minutes is preferably 6% or less, and more preferably 5% or less. If the heat shrinkage is 6% or less, plane defects such as curling and expansion during HC processing can be suppressed. It can be said that the lower the heat shrinkage, the better, but it is preferably -1% or more, and preferably 0% or more. The minus sign here means that expansion occurs after heating, and it may become a plane defect when it is less than -1%.

[0075] The polyester film for foldable display of the present invention can give sufficient pencil hardness to the hard coating film after laminating the hard coating layer. It can be considered that the conventional polyester film, after laminating the hard coating layer, has a reduced pencil hardness in the pencil hardness evaluation of the hard coating film due to deformation of the film in the thickness direction. In the present invention, by making the indentation depth after unloading the test force in the thickness direction of the film obtained by the dynamic ultramicrohardness tester described later a specific range, high hardness can be achieved in the pencil hardness evaluation of the hard coating film. The indentation depth after unloading the test force in the thickness direction of the film is preferably 1.5 μm or less, more preferably 1.4 μm or less, and further preferably 1.3 μm or less. When the indentation depth after unloading the test force (the final deformation after applying the load) is 1.5 μm or less, in the pencil hardness evaluation of the hard coating film after laminating the hard coating layer, the film is not easy to deform in the thickness direction, and the pencil hardness can be improved. If the pencil hardness of the hard coating film can be improved, scratches and pits are not easy to be generated on the display surface, and the visibility of the display is improved. It can be said that the lower the indentation depth after the test force is released, the better. However, from the perspective of stable production and gradual saturation of the effect, it is preferably 0.3 μm or more, and more preferably 0.5 μm or more.

[0076] In order to reduce the indentation depth after the test force is unloaded, it is effective to adjust the refractive index in the thickness direction to 1.520 or less. As a means to adjust the refractive index to 1.520 or less, as described later, the following conditions can be exemplified: within the range that can control the refractive index in the other physical properties, bending direction, and folding direction within the preferred range, the stretching ratio in the bending direction and folding direction is adjusted to a higher value; the stretching temperature in the bending direction and folding direction is set to a lower value; the heat setting temperature is set to a higher value, etc.

[0077] The elastic modulus in the bending direction of the polyester film as the substrate of the hard coat film and the laminated film is preferably less than 2.7GPa, more preferably less than 2.6GPa, and further preferably less than 2.5GPa. By reducing the elastic modulus in the bending direction, the stress applied to the hard coat layer can be reduced when the hard coat film (laminated film) is bent. It can be said that the lower the elastic modulus in the bending direction, the better the bending property, but because it will damage the planarity of the display surface, it is preferably more than 1.8GPa. The elastic modulus in the folding direction is preferably more than 4.5GPa, more preferably more than 4.6GPa, and further preferably more than 4.7GPa. By increasing the elastic modulus in the folding direction, the planarity of the display surface can be maintained when the display is made. The higher the elastic modulus in the folding direction, the more preferred, but from the viewpoint of film forming properties, it is preferably less than 8.0GPa.

[0078] The surface of the polyester film of the present invention may be treated to improve adhesion with a resin forming a hard coat layer, etc. The non-hard coat surface of the hard coat film of the present invention may be coated with an adhesive or subjected to other treatments to improve adhesion with a hard coat layer.

[0079] Examples of the surface treatment method include: convexo-concave treatment by sandblasting, solvent treatment, etc., corona discharge treatment, electron beam irradiation treatment, plasma treatment, ozone / ultraviolet irradiation treatment, flame treatment, chromic acid treatment, oxidation treatment such as hot air treatment, and the like, which can be used without particular limitation.

[0080] In addition, adhesion can be improved by using an adhesion improving layer such as an easy adhesion layer. As the easy adhesion layer, acrylic resin, polyester resin, polyurethane resin, polyether resin, etc. can be used without particular limitation, and can be formed by a general coating technique, preferably a so-called in-line coating recipe.

[0081] The above-mentioned polyester film can be manufactured, for example, through the following steps: a polymerization step, in which the inorganic particles are uniformly dispersed in a monomer liquid that becomes a part of the polyester raw material and filtered, and then added to the remainder of the polyester raw material to polymerize the polyester; and a film forming step, in which the polyester is melt-extruded into a sheet through a filter, cooled and then stretched to form a substrate film.

[0082] Next, regarding the method for producing a biaxially stretched polyester film, an example of using pellets of polyethylene terephthalate (hereinafter, sometimes referred to as PET) as a raw material for a substrate film is described in detail, but the invention is not limited thereto. In addition, the number of layers such as a single-layer structure and a multi-layer structure is not limited.

[0083] After the pellets of PET are mixed and dried in a prescribed ratio, they are supplied to a known melt lamination extruder, extruded from a slit-shaped die into a sheet, and cooled and solidified on a casting roll to form an unstretched film. In the case of a single layer, one extruder may be used, and in the case of a multi-layer film, two or more extruders, a multi-manifold or a confluence block (e.g., a confluence block with a square confluence portion) may be used to laminate a plurality of film layers constituting each outermost layer, extrude a sheet of two or more layers from a nozzle, and cool it on a casting roll to form an unstretched film.

[0084] In the above case, during melt extrusion, it is preferred to perform high-precision filtration to remove foreign matter contained in the resin while the molten resin is maintained at an arbitrary position of about 280° C. The filter material used in the high-precision filtration of the molten resin is not particularly limited, and a filter material made of sintered stainless steel is preferred because it excels in removing aggregates having Si, Ti, Sb, Ge, and Cu as main components and high-melting-point organic matter.

[0085] Furthermore, the filter particle size (initial filtration efficiency 95%) of the filter material is preferably less than 20 μm, particularly preferably less than 15 μm. When the filter particle size (initial filtration efficiency 95%) of the filter material exceeds 20 μm, foreign matter larger than 20 μm cannot be fully removed. Although the high-precision filtration of the molten resin by using a filter material having a filter particle size (initial filtration efficiency 95%) of less than 20 μm may sometimes reduce productivity, it is preferred in terms of obtaining a film with fewer protrusions generated by coarse particles.

[0086] (Refractive index with respect to bending direction)

[0087] In the present invention, the refractive index of at least one of the longitudinal direction (mechanical flow direction) and the width direction of the polyester film is preferably 1.590 to 1.620, more preferably 1.591 to 1.600. In addition, the refractive index of the bending direction of the polyester film is preferably 1.590 to 1.620, more preferably 1.591 to 1.600. Here, the bending direction refers to Figure 2As shown by symbol 22 on the polyester film (symbol 2), it is a direction orthogonal to the folding portion (symbol 21) envisioned in the use of the foldable display. When the refractive index in at least one of the length direction and the width direction is 1.590 to 1.620, there is less deformation during repeated folding, and there is no worry about the image quality of the foldable display being reduced, which is preferred. The refractive index is more preferably 1.591 to 1.600. Of course, this direction is preferably the aforementioned bending direction. If it is above 1.590, there is no worry about cracks in the direction of the folding portion after the bending test described later, and of course no breakage occurs, so the visibility of the display can be maintained well. The refractive index of the polyester film can be effectively adjusted by adjusting the stretching ratio and the stretching temperature. In addition, in order to adjust the refractive index, a relaxation process in the stretching direction and multi-stage stretching can be used. In the case of multi-stage stretching, it is preferred to make the stretching ratio of the second stage and thereafter higher than the stretching ratio of the first stage.

[0088] By controlling the refractive index of at least one of the length direction (mechanical flow direction) and the width direction of the polyester film within the above range, and more preferably controlling the refractive index of the bending direction within the above range, fatigue caused by the compressive stress applied to the inner side of the fold when folding can be reduced. It is believed that fatigue caused by compressive stress mainly occurs in the crystal part, and the less crystals there are in the bending direction, the less fatigue is likely to occur. Therefore, it can be considered that by reducing the refractive index, the amount of oriented crystals in the bending direction is reduced, and compression fatigue is suppressed.

[0089] In addition, by reducing the refractive index, the creep phenomenon caused by the tensile stress applied to the outside of the fold during folding can be suppressed. It is believed that fatigue caused by tensile stress mainly occurs in the amorphous part, and the molecular chains are aligned due to the repeated stress, resulting in deformation. It can be inferred that when there are fewer molecular chains arranged in the bending direction, the deformation caused by alignment is less. In addition, when there are fewer amorphous parts, fatigue caused by stretching can be suppressed, so it is preferred that the crystallinity, that is, the density, is high.

[0090] In the present invention, for the unstretched polyester sheet, the stretching ratio in at least one of the length direction (mechanical flow direction) and the width direction is preferably set to 1.2 to 2.0 times, and more preferably 1.7 to 2.0 times. In addition, the stretching direction is preferably the aforementioned bending direction. When the stretching ratio is 1.2 times or more, there is no deformation in post-processing such as hard coating, so it is preferred. When the stretching ratio is 2.0 times or less, no uneven thickness of the film occurs, so it is preferred. As the stretching temperature, 75 to 120°C is preferred, and 75 to 105°C is more preferred. It should be noted that the heating method during stretching can adopt the previously known means such as hot air heating, roller heating, infrared heating, etc. By setting the stretching temperature to 75 to 120°C, the larger uneven thickness caused by stretching at the above-mentioned stretching ratio can be prevented. In addition, by stretching at a low temperature as low as possible within the range that does not produce the aforementioned large uneven thickness, the refractive index in the thickness direction can be reduced.

[0091] (Refractive index with respect to the direction of the folded portion)

[0092] The refractive index of the polyester film in the direction orthogonal to the direction with a refractive index of 1.590 to 1.620 is preferably 1.670 to 1.700. That is, the refractive index in the direction orthogonal to the bending direction (the direction of the folded portion) is preferably 1.670 to 1.700. By setting it to 1.670 to 1.700, the deformation during folding in the bending direction can be reduced. By setting it to less than 1.700, cracks or breaks in the direction of the folded portion can be suppressed. By setting it to more than 1.670, the bendability in the bending direction and the surface hardness can be improved. More preferably 1.680 to 1.695. As a method for adjusting the refractive index in the direction orthogonal to the bending direction, stretching ratio, stretching preheating temperature, stretching temperature, multi-stage stretching, and film relaxation can be listed. The stretching ratio is preferably 4.0 to 6.0 times, and more preferably 4.4 to 6.0. In addition, the stretching preheating temperature in the direction orthogonal to the bending direction is preferably 70 to 110°C. When multiple stretching is performed in a direction perpendicular to the bending direction, the stretching ratio in the second and subsequent stages is preferably higher than that in the first stage. The film may be relaxed by 1 to 10% in both the machine flow direction (length direction) and the perpendicular direction (width direction).

[0093] (Refractive index in the thickness direction)

[0094] The refractive index in the thickness direction is preferably 1.520 or less. This is because, by setting it to 1.520 or less, even if the refractive index in the bending direction is designed to be low, the reduction in the hardness of the film surface can be suppressed, and the bendability and surface hardness can be taken into account. By setting it to 1.520 or less, the indentation depth after the test force in the thickness direction is reduced, and the hardness of the film surface, especially the pencil hardness of the hard coating after the hard coating is laminated, can be improved. It is more preferably 1.515 or less, further preferably 1.510 or less, particularly preferably 1.505 or less, and most preferably 1.500 or less. It is preferred that the refractive index in the thickness direction is low, but from the perspective of stable production, it is preferably 1.3 or more, and then it can be 1.4 or more. It is particularly preferably 1.410 or more. It can be said that the above range can be achieved by increasing the stretching ratio in both the bending direction and the folding direction, but in order to control the refractive index in the bending direction and the width direction within a preferred range and control the refractive index in the thickness direction, it is preferred to set the conditions while confirming the balance of the conditions of each process of the film-making process.

[0095] The methods for controlling the refractive index in the thickness direction within the above range include: the stretching preheating temperature in the bending direction, the stretching temperature, the stretching ratio, the stretching preheating temperature in the direction of the folded portion, the stretching temperature, the multi-stage stretching, the high-ratio stretching, or the temperature setting of the heat setting. The stretching preheating temperature in the bending direction is preferably 70°C to 110°C. The stretching temperature in the bending direction is preferably 75 to 120°C. The stretching ratio in the bending direction is preferably 1.2 to 2.0 times, and more preferably 1.7 to 2.0 times. By lowering the stretching temperature and stretching at a low stretching ratio, the refractive index in the thickness direction can be effectively reduced while maintaining the bendability in the bending direction. The stretching preheating temperature in the folded portion direction is also preferably 75°C to 110°C. The stretching temperature is preferably 75 to 120°C. The stretching ratio of the folded portion is preferably 4.0 to 6.0 times, and more preferably 4.4 to 6.0 times. The refractive index in the bending direction can be maintained or reduced while effectively reducing the refractive index in the thickness direction. As a method of high-ratio stretching, multi-stage stretching can be used. At this time, it is preferred to make the stretching ratio of the second section higher than the stretching ratio of the first section so as to effectively control the refractive index. In addition, a method of stretching again after the crystallization step can also be used. It is also possible to use accelerated stretching in which the stretching speed is increased from the initial stage of stretching to the second half.

[0096] The heat setting temperature is preferably 180 to 240° C. By heat setting, oriented crystallization in the stretching direction proceeds, and the refractive index in the thickness direction can be reduced.

[0097] The reason why the hardness of the film surface is improved by reducing the refractive index in the thickness direction is not necessarily clear, but it is considered that aromatic groups such as benzene rings in the molecular chain are oriented in the plane direction, which has the effect of suppressing deformation caused by stress applied in the thickness direction.

[0098] (About the density of polyester film)

[0099] The density of the polyester film is preferably 1.380 g / cm 3 More preferably 1.383 g / cm 3 By setting it to 1.380g / cm 3 The density is preferably higher, and it also depends on the presence or absence of particles in the film, but 1.40 g / cm is preferred. 3 Below, more preferably 1.395 g / cm 3 By setting the heat setting temperature during film formation to 180-240°C, crystallization can be promoted and the density can be effectively increased. 3 If the thickness is less than 100 μm, crystallization is insufficient and deformation due to bending is likely to occur. In addition, the heat shrinkage rate is increased, and the processability during hard coating is deteriorated.

[0100] The bending direction of the polyester film preferably corresponds to the longitudinal direction (mechanical flow direction). As a result, it is easy to reduce the refractive index in the bending direction during biaxial stretching, and it is easy to improve the bendability. That is, a polyester film can be obtained in which the unstretched polyester sheet is preferably stretched at a stretching ratio of 1.2 to 2.0 times, more preferably 1.7 to 2.0 times, in the longitudinal direction. In addition, stretching at a stretching ratio of 4.0 to 6.0 times, more preferably 4.4 to 6.0 times, in the width direction can be said to be a preferred method.

[0101] In addition, in the present invention, it is particularly preferred that the polyester film has the following four properties at the same time:

[0102] (1) The refractive index in the bending direction is 1.590 to 1.620

[0103] (2) The refractive index in the direction of the folded portion is 1.670 to 1.700

[0104] (3) The refractive index in the thickness direction is 1.520 or less

[0105] (4) Density: 1.380 g / cm 3 above

[0106] However, even if the combination is within the range of the above-mentioned preferred manufacturing conditions, for example, the stretch ratio in the bending direction is 1.4 times or less, the stretch ratio in the folding direction is less than 4.4 times, and the heat setting temperature is 220°C or less, and the combination of conditions that cannot be said to be the best within the range of each preferred manufacturing condition, it may not necessarily be possible to obtain a polyester film that satisfies the above-mentioned four characteristics at the same time. In this case, by fine-tuning any of the conditions such as increasing the stretch ratio in the bending direction to 1.7 times or more, increasing the stretch ratio in the folding direction to 4.4 times or more, increasing the heat setting temperature to about 230°C, or lowering the stretching temperature in the bending direction and / or the folding direction, or by a combination thereof, the above-mentioned four characteristics can be satisfied at the same time.

[0107] In order to adjust the film forming properties, film strength, thermal dimensional stability, appearance defects, etc., any film forming method such as stretching, relaxation, heat setting, surface treatment, etc. can be adopted, but it can be said that controlling the refractive index and density of the film within the above preferred range is a particularly preferred method in the present invention. By controlling the refractive index and density within the preferred range, it is possible to provide a polyester film suitable for foldable displays that can obtain better bending resistance and surface hardness than existing films, especially high pencil hardness of the hard coating film after laminating the hard coating layer.

[0108] Specifically, for example, after the PET pellets are fully vacuum dried, they are supplied to an extruder, melt-extruded into a sheet at about 280°C and cooled to solidify to form an unstretched PET sheet. The obtained unstretched sheet is stretched to 1.2 to 2.0 times, more preferably 1.7 to 2.0 times, in the length direction with a roller heated to 75 to 120°C to obtain a uniaxially oriented PET film. Furthermore, the end of the film is gripped with a clamp and introduced into a hot air zone heated to 75 to 120°C. After drying, it is stretched to 4.0 to 6.0 times, more preferably 4.4 to 6.0 times in the width direction. Next, it can be introduced into a heat treatment zone at 180 to 240°C for 1 to 60 seconds of heat treatment. In this heat treatment process, a relaxation treatment of 0 to 10% can be performed in the width direction or the length direction as needed.

[0109] The intrinsic viscosity of the polyester film is preferably in the range of 0.50 to 1.0 dl / g. When the intrinsic viscosity is 0.50 dl / g or more, the impact resistance is improved and the internal circuit of the display is not easily broken due to external impact, which is preferred. On the other hand, when the intrinsic viscosity is 1.00 dl / g or less, the filter pressure of the molten fluid does not increase excessively, and the film production is stable, which is preferred.

[0110] When a polymer film with birefringence is arranged at a position closer to the viewing side than the display component and observed from an oblique direction, coloration and rainbow-like color spots (rainbow spots) sometimes occur. This is because a part of the light emitted from the display component is reflected at the interface to generate a polarized light component. When the polarized light component passes through the polyester film, it is converted into linear polarized light or elliptically polarized light orthogonal to the original polarized light by the in-plane retardation (Re) which is the product of the birefringence and thickness of the polymer film. The converted polarized light removes a part of the polarized light component due to reflection at the film-air interface, etc. The coloration and rainbow spots can be prevented by setting the in-plane retardation (Re) of the polyester film to more than 3000nm. This is because the pattern converted into linear polarized light or elliptically polarized light depends on the wavelength and the in-plane retardation (Re), but by increasing the in-plane retardation (Re), the pattern can be repeated within a short wavelength period. As a result, the envelope shape of the spectrum of the transmitted light can be made similar to the luminous spectrum of the light source, so that the human eye cannot distinguish.

[0111] The preferred lower limit of the in-plane retardation (Re) is 4500 nm, and the more preferred lower limit is 6000 nm.

[0112] On the other hand, the upper limit of the in-plane retardation (Re) is preferably 30000 nm from the viewpoint of the above-mentioned visibility (rainbow spot suppression). The upper limit of the in-plane retardation (Re) is more preferably 20000 nm, further preferably 15000 nm, particularly preferably 12000 nm, and most preferably 10000 nm.

[0113] It should be noted that the in-plane retardation (Re) of the polyester film of the present invention can be obtained by measuring the refractive index and thickness in the biaxial direction, or by using a commercially available automatic birefringence measuring device such as KOBRA-21ADH (manufactured by Oji Instruments Co., Ltd.). In addition, the slow axis direction can be obtained using a molecular orientation meter (e.g., MOA-6004 molecular orientation meter manufactured by Oji Instruments Co., Ltd.).

[0114] The OLED light source used in the foldable display has a wide range of emission spectrum. Therefore, by setting the in-plane retardation (Re) of the polyester film to the above range, the envelope shape of the spectrum of the transmitted light can be made close to the emission spectrum of the light source only through a relatively simple structure.

[0115] When a polarizing plate is present on the viewing side of the display unit, the polyester film of the present invention is preferably disposed closer to the viewing side than the polarizing plate, because visibility is improved and a sufficient antireflection function can be obtained, which is preferred.

[0116] There is no particular restriction on the angle between the absorption axis of the polarizer and the slow axis of the polymer film. From the perspective of the convenience of cutting the polarizer and the polymer film, the angle between the absorption axis of the polarizer and the slow axis of the polymer film is preferably 0 degrees or 90 degrees. Furthermore, from the perspective of easily reducing coloration and rainbow spots even when the in-plane retardation (Re) is low, the angle between the absorption axis of the polarizer and the slow axis of the polymer film is preferably 0 degrees. At this time, it is preferably allowed to be within a range of ±20 degrees relative to 0 degrees or 90 degrees, and then within ±10. On the other hand, from the perspective of preventing the dark (blackout) when watching the screen while wearing polarized sunglasses, it is preferably more than 20 degrees and less than 70 degrees, and more preferably 30 to 60 degrees.

[0117] (Easy Adhesion Layer)

[0118] In the present invention, in order to improve the adhesion between the polyester film and the hard coating layer, etc., it is also preferred to laminate an easy-adhesion layer on the polyester film. The easy-adhesion layer can be obtained as follows: after applying the coating liquid for forming the easy-adhesion layer to one or both sides of an unstretched or longitudinally uniaxially stretched film, heat-treating and drying it as needed, and then stretching it in at least one direction that has not been stretched, thereby obtaining it. Heat treatment can also be performed after biaxial stretching. The final coating amount of the easy-adhesion layer is preferably managed to be 0.005 to 0.20 g / m 2 . The coating amount is 0.005g / m 2 On the other hand, the coating amount is 0.20 g / m 2 When the content is less than 50%, anti-blocking property can be obtained, which is preferred.

[0119] As the resin contained in the coating liquid used in the lamination of the easy-adhesive layer, for example, polyester resin, polyether polyurethane resin, polyester polyurethane resin, polycarbonate polyurethane resin, acrylic resin, etc. can be used without particular limitation. As the cross-linking agent contained in the coating liquid for forming the easy-adhesive layer, melamine compounds, isocyanate compounds, oxazoline compounds, epoxy compounds, carbodiimide compounds, etc. can be listed. Two or more kinds can be mixed and used respectively. They are preferably coated with water-based coating liquid in terms of the properties of the online coating, and the aforementioned resin and cross-linking agent are preferably water-soluble or water-dispersible resins and compounds.

[0120] In order to impart slipperiness to the easy-adhesive layer, it is preferred to add particles. The average particle size of the fine particles is preferably less than 2 μm. When the average particle size of the particles exceeds 2 μm, the particles are easy to fall off from the easy-adhesive layer. As particles contained in the easy-adhesive layer, for example, inorganic particles such as titanium oxide, barium sulfate, calcium carbonate, calcium sulfate, silicon dioxide, aluminum oxide, talc, kaolin, clay, calcium phosphate, mica, hectorite, zirconium oxide, tungsten oxide, lithium fluoride, calcium fluoride, styrene-based, acrylic acid-based, melamine-based, benzoguanamine-based, silicone-based, etc. can be listed. They can be added to the easy-adhesive layer alone, or two or more can be added in combination.

[0121] In addition, as the coating method of the coating liquid, a known method can be used in the same manner as the above-mentioned coating layer. For example, reverse roll coating, gravure coating, kiss coating, roller brushing, spraying, air knife coating, wire rod coating, tubular scraper method, etc. can be listed, and these methods can be carried out alone or in combination.

[0122] (Hard Coating)

[0123] When the polyester film of the present invention is used as a surface protection film located on the surface of a foldable display to protect the display, it is preferred that the polyester film has a hard coating on at least one surface. The hard coating is preferably located on the display surface side of the polyester film and used for the display. As the resin forming the hard coating, acrylic acid, siloxane, inorganic mixture, urethane acrylate, polyester acrylate, epoxy, etc. can be used without particular limitation. In addition, two or more materials can be mixed and used, and particles such as inorganic fillers and organic fillers can also be added.

[0124] (Film thickness of hard coat layer)

[0125] The film thickness of the hard coating layer is preferably 1 to 50 μm. If it is 1 μm or more, it is fully cured and the pencil hardness becomes high, which is preferred. In addition, by making the thickness less than 50 μm, the curling caused by the curing shrinkage of the hard coating layer can be suppressed, and the operability of the film can be improved.

[0126] (Coating method)

[0127] As the coating method of the hard coat layer, a Mayer rod, a gravure coater, a rod coater, a knife coater, etc. can be used without particular limitation, and it can be appropriately selected according to the viscosity and the film thickness.

[0128] (Curing conditions)

[0129] As a method for curing the hard coat layer, energy rays such as ultraviolet rays and electron beams, a curing method using heat, etc. can be used. In order to reduce damage to the film, a curing method using ultraviolet rays, electron beams, etc. is preferred.

[0130] (Pencil hardness)

[0131] The pencil hardness of the hard coat layer is preferably 3H or more, more preferably 4H or more. If the pencil hardness is 3H or more, it is not easy to scratch and visibility will not be reduced. Generally, the pencil hardness of the hard coat layer is preferably high, but it can be 9H or less, or 8H or less, and it can be used practically without any problem when it is 6H or less.

[0132] (Characteristics of hard coating)

[0133] The hard coat layer in the present invention can be used to increase the pencil hardness of the surface as described above and to protect the display, and preferably has a high transmittance. As the total light transmittance of the hard coat, it is preferably 85% or more, more preferably 87% or more, and further preferably 88% or more. When the transmittance is 85% or more, sufficient visibility can be obtained. The higher the total light transmittance of the hard coat, the more preferred it is. From the perspective of stable production, it is preferably 99% or less, and can be 97% or less. In addition, the haze of the hard coat is usually preferably lower, preferably 3% or less. The haze of the hard coat is more preferably 2% or less, and most preferably 1% or less. When the haze is 3% or less, the visibility of the image can be improved. The lower the haze, the better. From the perspective of stable production, it is preferably 0.1% or more, and can be 0.3% or more.

[0134] The hard coating layer may be further provided with other functions. For example, a hard coating layer provided with functions such as an anti-glare layer having a certain pencil hardness as described above, an anti-glare anti-reflection layer, an anti-reflection layer, a low-reflection layer, and an antistatic layer may be preferably used in the present invention.

[0135] In addition, a hard coating layer may be provided when used as a substrate film of a touch panel assembly. When an ITO layer is used as a transparent electrode layer of a touch panel assembly, a refractive index adjustment layer is preferably provided between the substrate film and the transparent electrode layer so that the electrode pattern is not easily visible. In this case, the hard coating layer itself may also serve as a refractive index adjustment layer, and a refractive index adjustment layer may also be laminated separately.

[0136] (Adhesive layer)

[0137] The polyester film as the substrate of the laminated film preferably has an adhesive layer on the opposite side of the side with the hard coating. As the material constituting the adhesive layer, there is no particular limitation, for example, existing adhesives such as rubber, acrylic, and polyolefin can be used. In the rubber system, natural rubber, butadiene rubber, isoprene rubber, and styrene block copolymer elastomers such as SBS, SIS, SEBS, and SEPS can be listed. In the acrylic system, substances obtained by crosslinking copolymers of methyl (meth) acrylate, ethyl (meth) acrylate, butyl (meth) acrylate, pentyl (meth) acrylate, hexyl (meth) acrylate, and 2-ethylhexyl (meth) acrylate can be listed. As a crosslinking agent, isocyanate compounds, epoxy compounds, metal chelating agents, compounds containing multiple double bonds, etc. can be listed. As a polyolefin system, ethylene-propylene rubbers such as EPM and EPDM can be listed; substances with them as soft segments and polyethylene and polypropylene as hard segments; blends of ethylene-propylene rubber and polyethylene and polypropylene, etc. By adding known tackifiers, softeners, etc. in the adhesive layer, it is possible to adjust the adhesiveness. In addition, by adjusting the molecular weight of the base polymer used, it is also possible to adjust the adhesiveness. The adhesive layer may further comprise other components. Examples of other components include additives (i.e., auxiliary agents), such as dyes, pigments, antistatic agents, antioxidants, light stabilizers, ultraviolet light absorbers, neutralizers, nucleators, epoxy stabilizers, lubricants, antibacterial agents, flame retardants, plasticizers, etc.

[0138] (Thickness of adhesive layer)

[0139] The thickness of the adhesive layer is 1 μm to 50 μm, preferably 2 μm to 40 μm, and more preferably 4 μm to 30 μm.

[0140] (Coating method)

[0141] The adhesive solution is applied and dried, and in the case of an acrylic system, a monomer or oligomer is applied and then cured by radiation. In addition, an optical adhesive sheet (OCA) without a substrate can be transferred.

[0142] The adhesive force (peel strength) is preferably changed according to the member to be attached. In a foldable display, if the adhesive force is weak, the problem of the bent portion floating occurs, so the adhesive force to the glass after 24 hours is preferably 10 to 40 N / 25 mm.

[0143] A release film may be provided on the surface of the adhesive layer (the side opposite to the polyester film).

[0144] (Release film)

[0145] As the release film of the adhesive sheet, it is suitable to use a film widely used as a release film. As the resin of the substrate film, there is no particular limitation, and if it is a material that becomes a resin film such as polyester, polycarbonate, polyamide, polyimide, polyamide-imide, polystyrene, triacetylcellulose, polypropylene, cyclic polyolefin, etc., it can be used without restriction. Among them, from the aspects of mechanical strength, heat resistance, supply stability, etc., polyester is preferred, and polyethylene terephthalate is further preferred. In addition, the film can be an unstretched film or a stretched film. In the case of a stretched film, it can be a uniaxially stretched film or a biaxially stretched film. Among them, a biaxially stretched polyethylene terephthalate film is preferred.

[0146] When the base film itself has mold release properties, it can be used as a mold release film as it is. In addition, in order to adjust the mold release properties, it can also be subjected to surface treatment such as corona treatment, plasma treatment, flame treatment, etc.

[0147] (Release layer)

[0148] Furthermore, a release layer may be provided on the substrate film. Examples of the release layer include silicone-based, amino resin-based, alkyd resin-based, and long-chain acrylic resin-based resins, and the composition and type thereof may be appropriately selected according to the desired release force.

[0149] When a release layer is provided, an easy-adhesion layer may be provided on the substrate film. As the easy-adhesion layer, films conventionally used in various substrate films such as polyester, acrylic, and polyurethane can be used, and the selection can be made according to the substrate film and release layer used.

[0150] (Antistatic layer)

[0151] The release film antistatic layer may be provided. Examples of the release layer antistatic agent include conductive polymers such as quaternary ammonium salts, polyaniline, and polythiophene, needle-shaped metal fillers, conductive high-refractive index fine particles such as tin-doped indium oxide fine particles and antimony-doped tin oxide fine particles, and combinations thereof.

[0152] As the binder resin, polyester, polyurethane, polyamide, acrylic, etc. can be used. The antistatic layer can be provided on the release surface as a lower layer of the release layer, or can be provided on the opposite side to the release surface.

[0153] Example

[0154] Next, the present invention will be described using Examples and Comparative Examples. First, the evaluation method of the characteristic values ​​implemented in the present invention is shown below.

[0155] (1) Intrinsic viscosity

[0156] The film or polyester resin was crushed and dried, and then dissolved in a mixed solvent of phenol / tetrachloroethane = 60 / 40 (mass ratio). The solution was centrifuged to remove inorganic particles, and then the flow time of the solution with a concentration of 0.4 (g / dl) and the flow time of the solvent alone were measured at 30°C using an Ubbelohde viscometer. From the ratio of these time, the intrinsic viscosity was calculated using the Huggins formula, assuming that the Huggins constant was 0.38.

[0157] (2) Bending resistance of polyester film samples (bending radius 1.5 mm)

[0158] Prepare a polyester film sample with a size of 20mm in width direction and 110mm in flow direction. Use a no-load U-shaped stretch tester (made by Yuasa System Equipment Co., Ltd., DLDMLH-FS) and set the bending radius to 1.5mm. Bend it 200,000 times at a speed of 1 time / second. At this time, for the sample, fix the position of 10mm at both ends of the long side, and set the bending part to 20mm×90mm. Here, Figure 1 This is a schematic diagram for illustrating the bending radius when a foldable display is folded. Consider the case where a polyester film is arranged on the inner surface of the folded state so as to Figure 1 The bending test was performed as a model so that the position of the symbol 11 was set to 1.5 mm. After the bending process was completed, the sample was placed on a flat surface with the inner side of the bend facing downward, and visually observed.

[0159] ○: No cracks or deformation were observed in the sample.

[0160] ×: There are cracks or creases in the sample, and the maximum height of the floating when placed horizontally is 5 mm or more.

[0161] (3) Bending resistance of polyester film samples (bending radius 0.5 mm)

[0162] The bending test was performed in the same manner as above, with the bending radius set to 0.5 mm and the bending was performed 200,000 times at a rate of 1 time / second. Figure 1 This is a schematic diagram showing the bending radius when a foldable display is folded. Consider the case where a polyester film is arranged on the inner surface of the folded state so as to Figure 1The bending test was carried out in a manner that the position of the symbol 11 was set to 0.5mm as a model. The film surface on the outside of the bending portion was observed with a digital microscope (RH8800 manufactured by HIROX Corporation) at 700 times magnification to observe the presence or absence of wrinkles (cracks). Independently from the above-mentioned visual test of bending resistance with a bending radius of 1.5mm, this test with the bending radius reduced to 0.5mm is carried out for the purpose of evaluating the folding display in a state close to the actual use state of the stacked or pasted hard coating or other components. It is independent of the visual observation based on the above-mentioned bending radius of 1.5mm, and is a test for detecting fine defects that are difficult to detect visually, i.e. defects that are easy to break or crack.

[0163] ○: The film surface on the outer side of the bend has no defects.

[0164] ×: Broken, or wrinkles (cracks) were observed on the film surface outside the bend.

[0165] (3) Bending resistance of hard coating film sample (laminated film) (bending radius 3.0 mm)

[0166] The hard coat film was bent 200,000 times at a rate of 1 time / second with a bending radius of 3.0 mm in the same manner as in the above bending test. When the hard coat layer was only on one side, the test was performed with the hard coat layer on the inside and the test with the hard coat layer on the outside.

[0167] ○: There are no cracks in the hard coating layer, and no deformation of the hard coating film is confirmed.

[0168] ×: The hard coating layer was broken, cracks were observed, or deformation of the hard coating layer was observed.

[0169] (4) Refractive index

[0170] According to JIS K 7142: 2008 "Method for determination of refractive index of plastics (Method A)", the refractive index in the longitudinal direction, the refractive index in the width direction, and the refractive index in the thickness direction were determined using an Abbe refractometer (manufactured by ATAGO CO., LTD., NAR-4T, measuring wavelength 589 nm).

[0171] (5) Pencil hardness

[0172] The pencil hardness of the hard coating film was measured as a sample at a load of 750 g and a speed of 1.0 mm / s in accordance with JIS K 5600-5-4: 1999. In the present invention, a pencil hardness of 3H or more was considered acceptable.

[0173] (6) Total light transmittance, haze

[0174] The measurement was performed using a haze meter (NDH5000, manufactured by Nippon Denshoku Industries, Ltd.).

[0175] (7) Density

[0176] The density was measured by the method in accordance with JIS K 7112:1999 (density gradient tube method). (Unit: g / cm 3 ).

[0177] (10) Tensile modulus (Young's modulus (unit: GPa))

[0178] The tensile modulus in the bending direction and the folding direction of the polyester film was measured at 23°C in accordance with JIS K7127:1999.

[0179] (8) Depth of penetration after test force unloading

[0180] The sample was cut into a square of about 2 cm and fixed on a micro cover glass 18×18 mm (Matsunami Glass Ind., Ltd.) with an adhesive (CEMEDINE (registered trademark) Hi-super 30) on the opposite side of the measurement surface. After being attached and fixed, it was left at room temperature for more than 12 hours, and then the indentation depth (μm) after the test force was unloaded was measured under the following conditions using a dynamic ultramicrohardness tester "DUH-211" (Shimadzu Corporation).

[0181] <<Measurement Conditions>>

[0182] Test mode: load-unload test

[0183] Use pressure head: 115 degree angle, triangular cone pressure head

[0184] Elastic modulus of indenter: 1.140×10 6 N / mm 2

[0185] Pressure head Poisson's ratio: 0.07

[0186] Test force: 50mN

[0187] Load speed: 4.44mN / sec

[0188] Load holding time: 2sec

[0189] Unloading holding time: 0sec

[0190] (9) Maximum thermal shrinkage

[0191] The sample film was cut into 10 mm in length and 250 mm in width, and marked at intervals of 200 mm along the direction of the long side to be measured. The marked interval A was measured under a constant tension of 5 g. Next, the sample film was placed in an oven at 150°C for 30 minutes without load, then taken out of the oven and cooled to room temperature. Then, the marked interval B was calculated under a constant tension of 5 g, and the heat shrinkage rate (%) was calculated using the following formula. It should be noted that the above heat shrinkage rate was measured at three equal positions along the width direction of the sample film, and the average value of the three points was taken as the heat shrinkage rate (%).

[0192] Thermal shrinkage (%) = [(AB) × 100] / A

[0193] The sample film was cut independently in both the bending direction and the folding direction so that the longitudinal and transverse directions were different and measured, and the data in the direction with the larger measured value was taken as the maximum heat shrinkage (%).

[0194] (10) In-plane retardation (Re)

[0195] It is a parameter defined by the product (△N×d) of the refractive index anisotropy of two orthogonal axes on the film (△N=|Nx-Ny|) and the film thickness d (nm), and is a measure of optical isotropy and anisotropy. The anisotropy (△N) of the refractive index of two axes is calculated by the following method. Using two polarizing plates, the orientation axis direction of the film is determined, and a 4cm×2cm rectangle is cut out in a manner orthogonal to the orientation axis direction as a sample for measurement. For this sample, an Abbe refractometer (manufactured by ATAGO CO., LTD., NAR-4T) is used to determine the refractive index of the two orthogonal axes (Nx, Ny) and the refractive index in the thickness direction (Nz), and the absolute value of the refractive index difference of the above two axes (|Nx-Ny|) is used as the anisotropy (△N) of the refractive index. The thickness d (nm) of the film was measured using an electronic micrometer (Millitron 1245D manufactured by Feinpruf GmbH) and the unit was converted into nm. The in-plane retardation (Re) was calculated from the product (ΔN×d) of the anisotropy of the refractive index (ΔN) and the thickness d (nm) of the film. It should be noted that the axis showing a larger refractive index among the above-mentioned orientation axes is defined as the slow axis.

[0196] (11) Observation of rainbow spots

[0197] The polyester film of the present invention was pasted on the surface of an OLED tablet (Samsung Galaxy Tab S3 SM-T820 9.7-Inch 32GB Tablet) with water so that the bending direction was aligned with the length direction of the tablet. The OLED tablet was set to display a white screen (R=0, G=0, B=0), and the angle was changed from the oblique direction relative to the normal direction of the display screen, and the display screen was rotated in the plane direction, and visual observation was performed to determine whether rainbow spots were generated as follows. The determination did not include color unevenness observed only in the tablet used.

[0198] ◎: No rainbow spots were generated from any direction.

[0199] ○: Very faint rainbow spots were observed in some directions.

[0200] △: Although only in some directions, faint rainbow spots can be observed in a slightly wider range.

[0201] ×: Although only in a certain direction, rainbow spots are clearly observed in a wide range.

[0202] (Preparation of polyethylene terephthalate pellets (a))

[0203] As the esterification reaction apparatus, a continuous esterification reaction apparatus consisting of a stirring device, a partial condenser, and a three-stage complete mixing tank with a raw material input port and a product output port was used. TPA was set to 2 tons / hour, EG was set to 2 mol relative to 1 mol of TPA, and antimony trioxide was set to an amount of Sb atoms of 160 ppm relative to the generated PET. These slurries were continuously supplied to the first esterification reactor of the esterification reaction apparatus, and reacted at 255°C under normal pressure with an average residence time of 4 hours.

[0204] Next, the reaction product in the first esterification reactor was continuously taken out of the system and supplied to the second esterification reactor, and EG distilled from the first esterification reactor was supplied to the second esterification reactor in an amount of 8% by mass relative to the produced polymer (produced PET), and further, an EG solution containing magnesium acetate in an amount of 65 ppm of Mg atoms relative to the produced PET and an EG solution containing TMPA in an amount of 20 ppm of P atoms relative to the produced PET were added, and the mixture was reacted at 260° C. at an average residence time of 1.5 hours under normal pressure. Next, the reaction product in the second esterification reactor was continuously taken out of the system and supplied to the third esterification reactor, and an EG solution containing TMPA in an amount of 20 ppm of P atoms relative to the produced PET was further added, and the mixture was reacted at 260° C. at an average residence time of 0.5 hours under normal pressure. The esterification reaction product generated in the third esterification reactor is continuously supplied to a three-stage continuous polycondensation reaction device for polycondensation, and then filtered using a stainless steel sintered filter material (nominal filtration accuracy 5 μm particles 90% cutoff) to obtain polyethylene terephthalate pellets (a) with an intrinsic viscosity of 0.62 dl / g.

[0205] (Preparation of polyethylene terephthalate pellets (b))

[0206] In the production process of the polyethylene terephthalate pellets (a), except that the residence time of the third esterification reaction was adjusted, the intrinsic viscosity was adjusted to 0.580 dl / g, thereby obtaining polyethylene terephthalate pellets (b).

[0207] (Preparation of polyethylene terephthalate pellets (c))

[0208] The polyethylene terephthalate pellets (a) were solid-phase polymerized in a rotary vacuum polymerization apparatus at 220° C. under a reduced pressure of 0.5 mmHg while varying the time to prepare polyethylene terephthalate pellets (c) having an intrinsic viscosity of 0.75 dl / g.

[0209] (Polymerization of urethane resin)

[0210] In a four-necked flask equipped with a stirrer, a Dimroth condenser, a nitrogen inlet tube, a silica gel drying tube, and a thermometer, 72.96 parts by mass of 1,3-bis(isocyanatomethyl)cyclohexane, 12.60 parts by mass of dimethylolpropionic acid, 11.74 parts by mass of neopentyl glycol, 112.70 parts by mass of polycarbonate diol with a number average molecular weight of 2000, and 85.00 parts by mass of acetonitrile and 5.00 parts by mass of N-methylpyrrolidone as solvents were added, and stirred for 3 hours at 75°C under a nitrogen atmosphere to confirm that the reaction liquid reached the specified amine equivalent. Then, after cooling the reaction liquid to 40°C, 9.03 parts by mass of triethylamine was added to obtain a polyurethane prepolymer D solution. Next, 450 g of water was added to a reaction container equipped with a high-speed stirring homogenizer, and the temperature was adjusted to 25°C, while stirring at 2000 min. -1 The isocyanate group-terminated prepolymer was added while stirring and mixing to disperse in water. Then, acetonitrile and part of the water were removed under reduced pressure to prepare a water-soluble polyurethane resin (A) having a solid content of 35% by mass.

[0211] (Polymerization of water-soluble carbodiimide compounds)

[0212] In a flask equipped with a thermometer, a nitrogen inlet tube, a reflux cooler, a dropping funnel and a stirrer, 200 parts by mass of isophorone diisocyanate and 4 parts by mass of 3-methyl-1-phenyl-2-phospholene-1-oxide as a carbodiimidization catalyst were added, and stirred at 180° C. for 10 hours under a nitrogen atmosphere to obtain isocyanate-terminated isophorone carbodiimide (polymerization degree = 5). Then, 111.2 g of the obtained carbodiimide and 80 g of polyethylene glycol monomethyl ether (molecular weight 400) were reacted at 100° C. for 24 hours. Water was slowly added thereto at 50° C. to obtain a yellow transparent water-soluble carbodiimide compound (B) having a solid content of 40% by mass.

[0213] (Preparation of coating liquid for forming an easily adhesive layer)

[0214] The following coating materials were mixed to prepare a coating solution.

[0215]

[0216] 0.1 parts by weight of a leveling agent (BYK307, manufactured by BYK Japan KK, concentration 100%) was added to 100 parts by weight of a hard coating material (Opstar (registered trademark) Z7503, manufactured by JSR Corporation, concentration 75%), and the mixture was diluted with methyl ethyl ketone to prepare a hard coating liquid a having a solid content concentration of 40% by weight.

[0217] (Example 1)

[0218] The pellets (a) of polyethylene terephthalate are supplied to the extruder and melted at 285°C. The polymer is filtered with a filter material of a stainless steel sintered body (nominal filtration accuracy 10μm particles 95% cutoff), extruded from a nozzle into a sheet, and then, by an electrostatic application casting method, contacted with a casting drum with a surface temperature of 30°C for cooling and solidification to prepare an unstretched film. The unstretched film is uniformly heated to 75°C with a heating roller, heated to 85°C with a non-contact heater, and 1.4 times roller stretching (longitudinal stretching) is performed. The above-mentioned coating liquid for forming an easy-adhesion layer is applied on both sides of the obtained uniaxially stretched film by roller coating, and then dried at 80°C for 20 seconds. It should be noted that the final (after biaxial stretching) dried coating amount is 0.06g / m 2 Then, it was introduced into a tenter and preheated at 105°C, stretched to 4.0 times in the transverse direction at 95°C, fixed in width, heat-set at 230°C for 5 seconds, and then relaxed by 4% in the width direction at 180°C to produce a polyethylene terephthalate film with a thickness of 50 μm. On one side of the produced film, a hard coating solution a was applied using a Mayer rod in such a way that the film thickness after drying became 5 μm, dried at 80°C for 1 minute, and irradiated with ultraviolet rays (accumulated light amount 200 mJ / cm 2 ) to obtain a hard coating film. Then, a double-sided adhesive sheet (manufactured by LINTEC Corporation., product name "OPTERIA MO-3006C", thickness: 25 μm) was attached to the side of the polyethylene terephthalate film not laminated with the hard coating layer to obtain a laminated film. The evaluation results are shown in Tables 1 and 2.

[0219] (Examples 2-3)

[0220] A polyester film, a hard coat film and a laminated film were obtained in the same manner as in Example 1 except that the stretching ratio in the longitudinal direction was changed to that described in Table 1.

[0221] (Example 4)

[0222] A polyester film, a hard coat film and a laminated film were obtained in the same manner as in Example 1 except that the stretching ratio in the width direction was changed to 4.4 times and the heat setting temperature was changed to 220°C.

[0223] (Examples 5-6)

[0224] Except having changed the stretching ratio in the longitudinal direction as described in Table 1, the same operation as in Example 4 was carried out to obtain a polyester film, a hard coat film and a laminated film.

[0225] (Example 7)

[0226] A polyester film, a hard coat film and a laminated film were obtained in the same manner as in Example 1 except that the stretching ratio in the width direction was changed to 5.5 times and the heat setting temperature was changed to 190°C.

[0227] (Examples 8 to 9)

[0228] Except having changed the stretching ratio in the longitudinal direction as described in Table 1, the same procedure as in Example 7 was carried out to obtain a polyester film, a hard coat film and a laminated film.

[0229] (Example 10)

[0230] A polyester film, a hard coat film and a laminated film were obtained in the same manner as in Example 5 except that a 10% relaxation heat treatment was performed at 100° C. after stretching in the longitudinal direction.

[0231] (Example 11)

[0232] In the manufacturing process of Example 5, the clamps were opened at 200°C after heat setting, and relaxation heat treatment was performed in the longitudinal direction and the width direction. The same operation as in Example 5 was performed to obtain a polyester film, a hard coating film, and a laminated film. The tenter speed and the winding roll speed were adjusted so that the relaxation rate in the longitudinal direction was 3%. The relaxation in the width direction was set to a free state.

[0233] (Example 12)

[0234] A polyester film, a hard coat film and a laminated film were obtained in the same manner as in Example 1 except that the temperature during the longitudinal stretching was changed to 75°C and the heat setting temperature was changed to 220°C.

[0235] (Example 13)

[0236] A polyester film, a hard coat film and a laminated film were obtained in the same manner as in Example 1 except that the temperature during stretching in the longitudinal direction was changed to 75° C. and the stretching ratio was changed to 1.2 times, and then the stretching ratio in the width direction was changed to 5.0 times.

[0237] (Example 14)

[0238] The same procedure as in Example 3 was followed except that the longitudinal stretching in Example 3 was performed in two stages, the stretching ratio in the first stage was set to 1.2 times, and the stretching ratio in the second stage was set to 1.67 times, to obtain a polyester film, a hard coating film, and a laminated film. The total stretching ratio in the longitudinal direction was about 2.0 times.

[0239] (Example 15)

[0240] A polyester film, a hard coat film and a laminated film were obtained in the same manner as in Example 5 except that the preheating temperature during the width direction stretching was changed to 95°C and the heat setting temperature was changed to 190°C.

[0241] (Example 16)

[0242] The stretching in the width direction of Example 2 was set to two stages, the stretching ratio of the first stage was set to 1.5 times, the stretching ratio of the second stage was set to 4.0 times, and the heat setting temperature was changed to 190° C. The same operation as Example 2 was performed to obtain a polyester film, a hard coating film, and a laminated film. The total stretching ratio in the width direction was 6.0 times.

[0243] (Examples 17-18)

[0244] The polyester film, hard coating film and laminated film were obtained in the same manner as in Example 2 except that the thickness was changed as described in Table 2. Here, the polyester film obtained in Example 17 may not necessarily give good results in the observation of rainbow spots, but the polyester film of the present invention can be used in all parts of foldable displays, for example, in applications such as a back protective film of a foldable display that is not related to rainbow spots, the polyester film obtained in Example 17 can be preferably used.

[0245] (Example 19)

[0246] A polyester film, a hard coat film and a laminated film were obtained in the same manner as in Example 1 except that no relaxation heat treatment in the width direction was performed in the production process of Example 1.

[0247] (Example 20)

[0248] After preparing an unstretched film in the same manner as in Example 1, the unstretched film was preheated at 75°C using a tenter and stretched transversely to 1.4 times at 85°C. The above-mentioned coating solution for forming an easy-adhesion layer was coated on both sides of the obtained uniaxially stretched film by a roller coating method, and then dried at 80°C for 20 seconds. It should be noted that the final (after biaxial stretching) dried coating amount was 0.06 g / m 2 The film was adjusted in the same manner as in Example 1. The film was heated uniformly to 105°C using a heating roller, heated to 95°C using a non-contact heater, and roller stretched (longitudinally stretched) to 4.0 times. The film was fixed in width and heat-set at 230°C for 5 seconds to obtain a polyethylene terephthalate film with a thickness of 50 μm. The subsequent steps were performed in the same manner as in Example 1 to obtain a hard coating film and a laminated film.

[0249] (Comparative Example 1)

[0250] A polyester film, a hard coat film and a laminated film were obtained in the same manner as in Example 1 except that stretching in the width direction was performed only as transverse uniaxial stretching without stretching in the longitudinal direction.

[0251] (Comparative Example 2)

[0252] A polyester film, a hard coat film and a laminated film were obtained in the same manner as in Example 7 except that stretching in the width direction was performed only as transverse uniaxial stretching without stretching in the longitudinal direction.

[0253] (Comparative Examples 3 to 7)

[0254] A polyester film, a hard coat film and a laminated film were obtained in the same manner as in Example 1 except that the heat setting temperature was changed to 220° C., the PET pellets described in Table 1 and the thickness described in Table 2 were used.

[0255] As described above, in Comparative Examples 3 to 7, the heat setting temperature is lower than that in Example 1, and the stretching ratios in the length direction and the width direction are within the preferred condition range, but the combination of the various condition levels cannot be said to be the best. As shown in Table 2, the refractive index in the thickness direction is increased, the indentation depth after the test force is unloaded is large, and the pencil hardness after laminating the hard coating is lower than that of the various Examples.

[0256] (Comparative Example 8)

[0257] A polyester film, a hard coat film and a laminated film were obtained in the same manner as in Example 1 except that the stretching ratio in the longitudinal direction was changed to 2.7 times and the heat setting temperature was changed to 220°C.

[0258] (Comparative Example 9)

[0259] A polyester film, a hard coat film and a laminated film were obtained in the same manner as in Example 1 except that the stretching ratio in the longitudinal direction was changed to 3.4 times.

[0260] (Comparative Example 10)

[0261] A polyester film, a hard coat film and a laminated film were obtained in the same manner as in Example 4 except that the heat setting temperature was changed to 100°C.

[0262] (Comparative Example 11)

[0263] A polyester film, a hard coat film and a laminated film were obtained in the same manner as in Example 13 except that the stretching temperature in the longitudinal direction was changed to 130°C.

[0264] (Comparative Example 12)

[0265] A polyester film, a hard coat film and a laminated film were obtained in the same manner as in Example 1 except that the preheating temperature in the width direction was changed to 120°C.

[0266] (Comparative Example 13)

[0267] A polyester film, a hard coat film and a laminated film were obtained in the same manner as in Example 13 except that the stretching ratio in the width direction was changed to 5.5 times and the heat setting temperature was changed to 230°C.

[0268] The laminated film of each example and comparative example was bonded to an organic EL device via a 25 μm thick adhesive layer to produce Figure 1 A foldable display of the smartphone type that can be folded in half at the entire center portion corresponding to a radius of 3 mm of the bending radius. The hard coating film is arranged on the surface of a continuous display via the folding portion so that the hard coating layer is located on the surface of the display. When the hard coating film of each embodiment is used, the movement and visibility of a smartphone that can be folded in half at the center and moved are satisfied. In addition, there is no situation where pits are generated on the surface due to external force. On the other hand, the foldable display using the hard coating film of each comparative example gradually feels image distortion in the folding portion of the display as the frequency of use increases, which is not preferred. In addition, pits and scratches are sometimes confirmed on the surface.

[0269] [Table 1]

[0270]

[0271] [Table 2]

[0272]

[0273] Industrial Applicability

[0274] The foldable display using the polyester film, hard coating film, and laminated film of the present invention maintains mass production, and the polyester film or hard coating film on the surface of the foldable display does not deform even after repeated folding, so that the image at the folded portion of the display does not suffer distortion. In particular, a mobile terminal device or image display device equipped with a foldable display using the polyester film, hard coating film, or laminated film of the present invention as a surface protection film provides beautiful images, is rich in functionality, and has excellent convenience such as portability.

[0275] Description of Reference Numerals

[0276] 1: Foldable display

[0277] 11: Bending radius

[0278] 2: Polyester film for surface protection film of foldable display

[0279] 21: Folding part

[0280] 22: Bending direction (direction perpendicular to the folded portion)

Claims

1. A polyester film for a foldable display, which is a polyester film having a thickness of 10 to 80 μm and satisfies the following conditions: (1) The refractive index in the bending direction is 1.590 to 1.620, (2) The refractive index in the direction of the folded portion is 1.670 to 1.700, (3) The refractive index in the thickness direction is less than 1.520, (4) Density: 1.380 g / cm 3 above, Here, the bending direction refers to a direction perpendicular to the folded portion when the polyester film is folded.

2. The polyester film for a foldable display according to claim 1, which has a total light transmittance of 85% or more, a haze of 3% or less, and a maximum heat shrinkage of 6% or less. 3 . The polyester film for a foldable display according to claim 1 , further comprising an easy-adhesion layer on at least one surface of the polyester film. 4 . The polyester film for a foldable display according to claim 1 , wherein the polyester film has an in-plane retardation (Re) of 3,000 to 30,000 nm. 5 . A hard coat film for a foldable display, comprising a hard coat layer having a thickness of 1 to 50 μm on at least one surface of the polyester film for a foldable display according to claim 1 . 6 . The hard coating film for a foldable display according to claim 5 , which has a total light transmittance of 85% or more.

7. The hard coating film for a foldable display according to claim 5 or 6, wherein: The elastic modulus of the polyester film in the bending direction is 2.7 GPa or less, and the elastic modulus in the folding direction is 4.5 GPa or more. 8 . The hard coat film for a foldable display according to claim 5 , which has a haze of 3% or less. 9 . A laminate film for a foldable display, comprising an adhesive layer on the surface of the hard coat film according to claim 5 , which surface is opposite to the surface having the hard coat layer.

10. The laminate film for a foldable display according to claim 9, wherein: The thickness of the adhesive layer is 1 to 50 μm.

11. A foldable display, comprising the hard coating film for a foldable display according to any one of claims 5 to 8 as a surface protection film arranged so that a hard coating layer is located on the surface, and a single hard coating film is arranged continuously across a folded portion of the foldable display.

12. A foldable display, comprising the laminate film for a foldable display according to claim 9 or 10 as a surface protection film arranged so that a hard coating layer is located on the surface, and a continuous single laminate film arranged across a folded portion of the foldable display.

13. A mobile terminal device comprising the foldable display according to claim 11 or 12.

Citation Information

Patent Citations

  • Method of processing hard coat film, hard coat film and protective film

    JP2010228391A

  • Manufacturing method for foldable hard coating film

    JP2016155124A

  • Polyester film and applications thereof

    WO2018150940A1